Synthesis of benzoheterocycles by palladium-catalyzed migratory cyclization through an unexpected reaction cascade - Wen-Cong Li; Lin Zhang; Shiming Bai; Jia-Hao Zhao; Guang-Rui Liu; Yu Lan; Shufeng Chen; Jialin Ming (Nature Communications)
Abstract Migratory functionalization of C–H bonds through metal migration from carbon to carbon under transition metal catalysis is a process of significant academic and industrial interest. Herein, a palladium-catalyzed migratory cyclization of α-bromoalkene derivatives ArXCBr=CH2, in which X denotes a phosphorus (P(O)R), silicon (SiR2), sulfur (SO2), carbon (C(O)), nitrogen (NTs), or oxygen-based moiety, affording various benzoheterocyclic compounds has been developed. Mechanistic investigations have demonstrated that the cyclization reaction proceeds through an unexpected cascade, with trans-1,2-palladium migration between sp2 carbons being a key step of catalytic cycle. To the best of our knowledge, this type of metal migration has not been reported previously.